Antidepressant activity of Simvastatin in behavioral models of depression in rats - Patke, Archit; Tripathi, Rakhi; Patke, Vinay Govind; Sonawane, Dipesh; Rege, Nirmala (International Journal of Research in Medical Sciences, 2017)
Background: There is evidence, that statins can augment the antidepressant effects of fluoxetine in rats. Hence the present experimental study was designed to evaluate the effect of Simvastatin on duration of immobility in acute forced swim test (Acute FST) and Chronic forced swim test (Chronic FST), as models of behavioral despair in rats. Methods: In acute FST and Chronic FST models, effects of simvastatin (Smv) and fluoxetine (Flx) per se and in combination, on immobility of rats were compared. Open field test was performed to discriminate between the general behavioral stimulation and antidepressant effect of study drugs. Results: In Acute FST, duration of immobility decreased (171.33 ± 6.15 sec) non-significantly in simvastatin group, & decreased significantly in the groups of rats which received fluoxetine alone (161.33 ± 8.68, P < 0.01) or in combination with simvastatin (167.66 ± 7.71 sec, P < 0.001). The 3 treatment groups did not differ from each other. In chronic FST duration of immobility lowered significantly in both, the fluoxetine treated group (147.66 ± 8.73) and the combination treated group (130.5 ± 5.68 sec) with significant fall in the combination group (P < 0.001) compared to the individual therapy groups. Conclusions: Lowering cholesterol levels with statins not only reduces risks for cardiovascular events, but also affect serotonergic neurotransmission, leading to clinical efficacy of standard antidepressants. Simvastatin can augment the antidepressant effects of fluoxetine in rats, raising the possibility that statins could be used to facilitate the effects of antidepressants in humans.